Human monoclonal antibodies inhibit invasion of transgenic Plasmodium knowlesi expressing Plasmodium vivax Duffy binding protein - Watson, QD; Carias, LL; Malachin, A; Redinger, KR; Bosch, J; Bardelli, M; Baldor, L; Feufack-Donfack, LB; Popovici, J; Moon, RW; Draper, SJ; Zimmerman, PA; et al. (BioMed Central, 2023)
Background: Plasmodium vivax has been more resistant to various control measures than Plasmodium falciparum malaria because of its greater transmissibility and ability to produce latent parasite forms. Therefore, developing P. vivax vaccines and therapeutic monoclonal antibodies (humAbs) remains a high priority. The Duffy antigen receptor for chemokines (DARC) expressed on erythrocytes is central to P. vivax invasion of reticulocytes. P. vivax expresses a Duffy binding protein (PvDBP) on merozoites, a DARC ligand, and the DARC: PvDBP interaction is critical for P. vivax blood stage malaria. Therefore, PvDBP is a leading vaccine candidate for P. vivax and a target for therapeutic human monoclonal antibodies (humAbs). Methods: Here, the functional activity of humAbs derived from naturally exposed and vaccinated individuals are compared for the first time using easily cultured Plasmodium knowlesi (P. knowlesi) that had been genetically modified to replace its endogenous PkDBP orthologue with PvDBP to create a transgenic parasite, PkPvDBPOR. This transgenic parasite requires DARC to invade human erythrocytes but is not reticulocyte restricted. This model was used to evaluate the invasion inhibition potential of 12 humAbs (9 naturally acquired; 3 vaccine-induced) targeting PvDBP individually and in combinations using growth inhibition assays (GIAs). Results: The PvDBP-specific humAbs demonstrated 70–100% inhibition of PkPvDBPOR invasion with the IC50 values ranging from 51 to 338 µg/mL for the 9 naturally acquired (NA) humAbs and 33 to 99 µg/ml for the 3 vaccine-induced (VI) humAbs. To evaluate antagonistic, additive, or synergistic effects, six pairwise combinations were performed using select humAbs. Of these combinations tested, one NA/NA (099100/094083) combination demonstrated relatively strong additive inhibition between 10 and 100 µg/mL; all combinations of NA and VI humAbs showed additive inhibition at concentrations below 25 µg/mL and antagonism at higher concentrations. None of the humAb combinations showed synergy. Invasion inhibition efficacy by some mAbs shown with PkPvDBPOR was closely replicated using P. vivax clinical isolates. Conclusion: The PkPvDBPOR transgenic model is a robust surrogate of P. vivax to assess invasion and growth inhibition of human monoclonal Abs recognizing PvDBP individually and in combination. There was no synergistic interaction for growth inhibition with the humAbs tested here that target different epitopes or subdomains of PvDBP, suggesting little benefit in clinical trials using combinations of these humAbs.